2022
DOI: 10.31557/apjcc.2022.7.2.267-272
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Nilotinib as Second Line Therapy for Chronic Myeloid Leukemia Patients in Karbala Province of Iraq

Abstract: Background: Second line treatment of chronic myeloid leukemia (CML) is crucial after imatinib therapy failure. In Iraq, nilotinib is the only available second line tyrosine kinase inhibitors (TKIs), making management of CML patients with failure response to 1st generation TKIs as a great challenge to the health system. Objectives: Our study tries to evaluate nilotinib safety and efficacy among CML patients in Karbala province of Iraq as the only drug available as second line treatment for CML patients post ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The survival rate of our study is quite comparable with the previous study with the imatinib as a frontline (IRIS study) which showed the OS rate at 83.3% (Hochhaus et al, 2017) and another study with frontline imatinib which showed the 10 year OS at 82% (Hehlmann et al, 2017). The previous study with nilotinib and dasatinib as second-line therapy after imatinib treatment also reported a long-term OS between 77-78% which was following our study (Giles et al, 2013;Shah et al, 2014;Mjali et al, 2022).…”
Section: Long-term Clinical Outcomes Including Os and Efssupporting
confidence: 89%
“…The survival rate of our study is quite comparable with the previous study with the imatinib as a frontline (IRIS study) which showed the OS rate at 83.3% (Hochhaus et al, 2017) and another study with frontline imatinib which showed the 10 year OS at 82% (Hehlmann et al, 2017). The previous study with nilotinib and dasatinib as second-line therapy after imatinib treatment also reported a long-term OS between 77-78% which was following our study (Giles et al, 2013;Shah et al, 2014;Mjali et al, 2022).…”
Section: Long-term Clinical Outcomes Including Os and Efssupporting
confidence: 89%